2022
DOI: 10.1093/ckj/sfac159
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality after kidney transplantation in mildly frail recipients

Abstract: Background Physical Frailty Phenotype (PFP) is the most used frailty instrument among kidney transplant recipients, classifying patients as pre-frail if they have 1–2 criteria and as frail if they have ≥ 3. However, different definitions of robustness have been used among renal patients, including only those who have 0 criteria, or those with 0–1 criteria. Our aim was to determine the impact of one PFP criterion on transplant outcomes. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The mean ages were 44 to 63 years, and the proportions of men were 53 to 71%. Physical Frailty Phenotype (PFP) was the mostly used assessment tool for frailty, which were used in eight studies [ 19 22 , 24 , 27 , 30 , 31 ]. Other evaluating tools for frailty were also used, such as short physical performance battery (SPPB) [ 23 ], Frailty Risk Score (FRS) [ 25 ], the Groningen Frailty Indicator (GFI) [ 26 ], the Inflammatory-Frailty Index (IFI) [ 29 ], and the new physical frailty phenotype (nPFP) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean ages were 44 to 63 years, and the proportions of men were 53 to 71%. Physical Frailty Phenotype (PFP) was the mostly used assessment tool for frailty, which were used in eight studies [ 19 22 , 24 , 27 , 30 , 31 ]. Other evaluating tools for frailty were also used, such as short physical performance battery (SPPB) [ 23 ], Frailty Risk Score (FRS) [ 25 ], the Groningen Frailty Indicator (GFI) [ 26 ], the Inflammatory-Frailty Index (IFI) [ 29 ], and the new physical frailty phenotype (nPFP) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a Spanish study that specifically addressed this methodological question found that the presence of even a single PFP frailty component (score 1) has an independent impact on KTR survival, a correlate of frailty, after transplantation [ 17 ]. Based on this finding, we used the original PFP criteria as in geriatrics, where a patient is considered robust/non-frail only if no PFP components are present [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence indicates that kidney recipients with even mild frailty have increased mortality. A large retrospective study of 296 kidney recipients, after conducting multivariate analysis, reported that patients identified as having only one PFP frailty criterion (mild frailty) had an increased risk of mortality post-transplantation [HR 3.52, 95% CI: 1.03-15.9, p = 0.048] [41].…”
Section: Discussionmentioning
confidence: 99%